The Relationship Between MAIAC Smoke Plume Heights and Surface PM. Issue 17 (4th September 2020) - Cheeseman, M.; Ford, B.; Volckens, J.; Lyapustin, A.; Pierce, J. R.
Abstract: Biomass burning is a source of fine particulate matter (PM2.5 ) air pollution, which adversely impacts human health. However, quantifying the health effects from biomass burning PM2.5 is difficult. Monitoring networks generally lack the spatial density needed to capture the heterogeneity of biomass burning smoke. Satellite aerosol optical depth (AOD) can be used to fill spatial gaps but does not distinguish surface‐level aerosols. Plume height (PH) observations may provide constraints on the vertical distribution of smoke and its impact on surface concentrations. We assessed PH characteristics from Multi‐Angle Implementation of Atmospheric Correction (MAIAC) and evaluated its correlation with colocated PM2.5 and AOD measurements. PH is generally highest over the western United States. The ratio PM2.5 :AOD generally decreases with increasing PH:PBLH (planetary boundary layer height), showing that PH has the potential to refine surface PM2.5 estimates for collections of smoke events. Plain Language Summary: Smoke from wildland and agricultural fires can rise high into the air or remain near the ground. This smoke height plays a major role in dictating the air quality of places downwind of fires, although these heights have been challenging to predict. Measurements from satellites are now routinely used to evaluate surface air quality. However, the satellite products commonly used in surface air quality analysis do not distinguish lofted smoke from surface smoke, leading to uncertainties in surface air quality during smoke events. We use a recently developed satellite product of smoke height to determine if these smoke‐height measurements can aid in surface air quality estimates. We also investigate how smoke plumes behave differently across the United States by counting the number of high‐altitude smoke observations over each state. Key Points: Satellite‐retrieved smoke plume heights have the potential to constrain surface particulate concentrations during biomass burning events Plume height is positively correlated with aerosol optical depth The ratio of surface particulate matter and aerosol optical depth decreases with the increasing ratio of plume to boundary layer heights